Clients Perception of Family Physician Working in a Family Medicine Centre in Baghdad - Habib, Huda A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Patient evaluation of the healthcare provided by his/her family doctor is a multidimensional concept, its main component being the doctor-patient interaction.Materials and Methods: a total of 200 client chosen by systematic random sampling were successfully interviewed immediately after having the contact with the family physician in the family medicine center.Results: The present study showed that the majority of the clients were young age, most of them were female, completed secondary education and the majorities were unemployed. This study determined the client general satisfaction the services provided by the physician the overall satisfaction was high (98%), the most significant statistical association was found between general satisfaction and the client age, gender and education. The evaluation of the physician interaction to the client was mostly positive regarding the doctor courtesy and humaneness, skills and continuity of care, comprehensiveness of care, in formativeness and doctor advice. Regarding client preferences most of the clients prefers female doctor, family physician specialty, and prefers being checked by the same doctor in each visit.Conclusion the client generally was satisfied with the services provided by the physician, a strong statistical association was found between satisfaction and some client sociodemographiccharacteristics like age, gender and the level education.